Association of Sleep Duration with Weight Gain and General and Central Obesity Risk in Chinese Adults: A Prospective Study. Issue 2 (26th December 2019) - Ning, Xuejuan; Lv, Jun; Guo, Yu; Bian, Zheng; Tan, Yunlong; Pei, Pei; Chen, Junshi; Yan, Shichuan; Li, Huimei; Fu, Zhifang; Chen, Yiping; Du, Huaidong; et al.
Abstract : Objective: Evidence on the association between sleep duration and obesity among adults is inconsistent. Prospective studies investigating the association in Chinese adults have been limited. This study aims to prospectively evaluate sleep duration in relation to subsequent weight gain and general and central obesity risk among Chinese adults. Methods: A total of 21, 958 participants aged 30 to 79 years reported their daily sleep duration. Obesity indicators were objectively measured; then significant weight gain (≥ 5 kg) and general and central obesity were modeled as the outcome. Logistic regression models were used to estimate odds ratios and 95% CIs. Results: Average sleep duration was 7.5 hours at baseline. During 8.0 ± 0.8 years of follow‐up, participants who reported sleeping ≤ 6 hours had higher risk for significant weight gain than those who slept 7 hours (multivariable‐adjusted odds ratio: 1.13; 95% CI: 1.02‐1.29). The association was stronger among those who were physically inactive at baseline ( P  = 0.04 for interaction). Short sleep duration was also associated with subsequent incident central obesity, with odds ratio of 1.13 (95% CI: 1.00‐1.28), but not with incident general obesity ( P  = 0.31). Conclusions: Compared with those who slept 7 hours per day, short sleepers had an increased risk of significant weight gain and central obesity.